Constructivism has failed to shift the IR agenda from that which older dominant schools determined. A discussion. - Giannakarou, Georgia (Journal of Eastern European and Central Asian Research (JEECAR), 2016)
Georgia Giannakarou University of Cambridge, UK ABSTRACT Whether Constructivism is considered a solid paradigm or just an approach in International Relations (IR) Domain – a verdict which is quite too soon to be reached, I suppose, it is undoubtedly a well-promising school of thought in IR. And whether Constructivism has failed to shift the IR agenda from that which older dominant schools determined or not, it is more than evident that this constitutes a still open question in both research and academic areas. In the first part of this essay, I refer to the rise and evolution of Constructivism from the 1980s up to date highlighting its origins and its core principles, while in the second part, more attention is been given to its dynamic dialogue with other dominant schools of IR and Political Science. The scope of this essay is to illuminate a great number of arguments already made both against and in favor of Constructivism, as presented in a certain variety of papers and works in the wider field of IR. Furthermore, this illumination is being held under the light of a dual source, provided by the prominent IR Theory and the International Security sub-field. A third part of this essay is devoted to the latter. I conclude that Constructivism’s power lies in its ‘weaknesses’, namely its interpretation of world politics through culture and identity, especially in the currently world instability caused by the global identity crisis and spreading ISIS radical fanaticism.